Four-Tier Test Based On Local Wisdom to Analyze Misconceptions in Rotational Dynamics - Ziyana Walida Prama; Qisthi Fariyani; Joko Budi Poernomo (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2022)
This RD research resulted in a four-tier diagnostic test instrument based on local wisdom. The purpose of the study was to describe the instrument's characteristics, test the validity, reliability, and characteristics of the items developed, and describe the misconception profile of the students of MA Islamiyyah Attanwir Talun. The development method uses the Borg Gall model with sample selection through purposive sampling. Data collection techniques include tests, interviews, questionnaires, and documentation. The test instrument was made by correlating physics material and the local wisdom of the community. The validity test results by the expert stated that the instrument developed was valid. The reliability of the developed instrument is 0.978. The test instrument consisted of 15 moderate and 13 difficult questions; with differentiating power, 12 items were corrected, seven were accepted but had to be corrected, and nine were accepted without improvement. There were 50% misconceptions about the answer, 57.14% about the reason, and 50% about the answer and reason. The highest misconception occurs in the concept of applying the moment of inertia, with a percentage of 67.23%. The lowest misconception is found in the concept of rigid body equilibrium, with a percentage of 38.98%.